IC 9421 A Manganese Consumption And Recycling Flow Model - Jr. Gabler (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Because of concern over the availability and reliability of an uninterrupted supply of manganese and other materials, the U.S. Congress requested that the U.S. Bureau of Mines (USBM) study the /low of strategic and critical materials in the economy to delineate and quantify the production areas where metal values are lost. As a result, the USBM developed a generic computerized commodity flow model that is readily amenable to updating. The original model developed for cobalt, with slight modifications, was used to track the flow of manganese. This report follows the flow of manganese through its metallurgical and chemical applications and highlights areas where significant losses occur owing to downgrading, export, or disposal. The study indicates that materials containing 695,000 short tons (st) of manganese were consumed domestically in 1990. Scrap recovery specifically for manganese recycling was insignificant. However, considerable manganese was recycled through processing operations as a minor component of ferrous and nonferrous scrap and steel slag. The major loss category is manganese lost in steel processing, 323,156 st or 46 pet of the 1990 apparent consumption. Most of this loss reports to steelmaking slags. Recovery from slags is technically feasible, but is not economically feasible.